Mechanistic modelling of tyrosine recombination reveals key parameters determining the performance of a CAR T cell switching circuit. Issue 1 (24th March 2020) - Bowyer, Jack E.; Chakravarti, Deboki; Wong, Wilson W.; Bates, Declan G.
Abstract : Inducible genetic switches based on tyrosine recombinase‐based DNA excision are a promising platform for the regulation and control of chimeric antigen receptor (CAR) T cell activity in cancer immunotherapy. These switches exploit the increased stability of DNA excision in tyrosine recombinases through an inversion–excision circuit design. Here, the authors develop the first mechanistic mathematical model of switching dynamics in tyrosine recombinases and validate it against experimental data through both global optimisation and statistical approximation approaches. Analysis of this model provides guidelines regarding which system parameters are best suited to experimental tuning in order to establish optimal switch performance in vivo. In particular, they find that the switching response can be made significantly faster by increasing the concentration of the inducer drug 4‐OHT and/or by using promoters generating higher expression levels of the FlpO recombinase.